Wireless Communication for Flying Cars - Saeed, Nasir; Al-Naffouri, Tareq Y.; Alouini, Mohamed-Slim (Frontiers in Communications and Networks, 2021)
Current ground-based transportation systems are subject to various challenges, including the high cost of infrastructure development, limited land space, and a growing urban population. Therefore, the automotive and aviation industries are collaborating to develop flying cars, also known as electric-vertical-takeoff-and-landing-aircrafts (eVTOLs). These eVTOLs will allow for rapid and reliable urban and suburban transportation. Safe operation of eVTOLs will require well-developed wireless communication networks; however, existing communication technologies need enhancement in order to provide services to flying cars. We describe several potential innovations that make communication between eVTOLs and the ground feasible. These innovations include three-dimensional cellular networks on-ground, tethered balloons, high altitude platforms, and satellites.